If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2j + -11j = -9 Combine like terms: 2j + -11j = -9j -9j = -9 Solving -9j = -9 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Divide each side by '-9'. j = 1 Simplifying j = 1
| -19.4-3(2*-19.4-7)= | | 5log(x-2)=10 | | y=5x^2+14x+1 | | 4(0)+n=10 | | 2d+4c=11 | | 10q-9q=17 | | (2x-8)-.5(9-4x)+2.5= | | 2(q+6)-4=2 | | 2x^2-5x+82=0 | | 9t+8=10t | | 10h+2h-8h=16 | | -7x+5=-12+4 | | -n^2+16n-34=-4n^2+1 | | 6=9(3+7f) | | -2(q+9)=2 | | 3/8=a/8 | | -5p+17=-18 | | 4(3x-1)=5x+6 | | 4/15-2/3 | | (x/2)-15=125 | | 2z-2x+2y+2z^3=0 | | -.75x+6=-12 | | 1h+7=17 | | v(x)=(12-2x)(16-2x)(x) | | 10k-11k=20 | | 0x+2y+2z=0 | | -2x+x-5=3x+3 | | k(x)=3(x-1)(x+1) | | 1.06(1.26)(7-x)=8 | | -3r+7-7=13-7 | | 1.06(1.26)77-x=8 | | (2x^2)+2+14x=90 |